Evidence on access to healthcare information by women of reproductive age in low- and middle-income countries: Scoping review - Shatilwe, Joyce Twahafifwa; Kuupiel, Desmond; Mashamba-Thompson, Tivani P. (PloS one, 2021)
A majority of women of reproductive age in low- and middle-income countries (LMICs) are not able to access healthcare information due to different factors. This scoping review aimed to map the literature on access to healthcare information by women of reproductive age in LMICs. The literature search was conducted through the following databases: Google Scholar, Science Direct, PubMed, EBSCOhost (Academic search complete, CINAHL with full text, MEDLINE with full text, MEDLINE, and PsycINFO), Emerald, Embase, published and peer-reviewed journals, organizational projects, reference lists, and grey literature. A total of 377 457 articles were identified from all the databases searched. Of these, four articles met inclusion criteria after full article screening and were included for data extraction. The themes that emerged from our study are as follows: accessibility, financial accessibility/affordability, connectivity, and challenges. This study demonstrated that there are minimal interventions that enable women of reproductive age to access healthcare information in terms of accessibility, financial accessibility, and connectivity. The findings of the study revealed poor access and utilization of healthcare information by women of reproductive age. We, therefore, recommend primary studies in other LMICs to determine the accessibility, financial accessibility, connectivity, and challenges faced by women of reproductive age in LMICs.